Numerical modeling of radiation-induced charge neutralization in MOS devices. (April 2022) - Sambuco Salomone, L.; Garcia-Inza, M.; Carbonetto, S.; Lipovetzky, J.; Redin, E.; Faigón, A.
Abstract: Radiation-induced charge neutralization at different bias is studied for 230 nm p-channel MOS dosimeters under γ-radiation. A physics-based numerical model is employed to reproduce the experimental results. Good agreement is obtained between measurements and simulations considering capture and neutralization rates independent of electric field during neutralization stages. Sensitivity curves during neutralization stages show a two part process consisting of a slow decrease for short times followed by a rapid fall. Remarkably, the model predicts this behavior and allows to understand that in terms of the potential well generated due to trapped holes within the oxide. Highlights: The response of a MOS dosimeter under γ-radiation was characterized. Measured sensitivity during neutralization stages showed a two part process. A physics-based numerical model predicts the sensitivity during neutralization. Charge neutralization at the potential well drives threshold voltage recovery.